The Landscape of CO₂ Emissions Across Africa: A Comparative Perspective - Jaime de Melo; Jean-Marc Solleder (Fondation pour les études et recherches sur le développement international (FERDI), 2022)
Expansion of Global Value Chains (GVCs) is a mixed blessing for the environment. Effects of growth and emissions from transport associated with international trade have negative effects; but greater flows of knowledge and associated spillovers, and adoption of environmentally innovative products have positive effects. This paper provides evidence on carbon dioxide (CO2) emissions for 51 African and 132 other countries for 163 products over the period 1995‒2015. The resulting landscape is summarized in four patterns. Patterns identified for the Africa region differ from those identified for other regions but are closely related to a synthetic aggregate comparator constructed on the basis of three characteristics (per capita income, share of manufacturing in GDP, and distance to trading partners). 1: All regions have reduced emission intensities over the period 1995‒2015. Africa's share of global CO2 emissions has remained constant over the period 1995‒2015. Asia, already the region with the largest share of global emission in 1995, has strengthened its leading polluter position. Europe and the Americas have reduced their share of emissions by nine and eight percentage points, respectively. Asia is decarbonizing; Africa not yet. 2: Carbon intensity of production has increased in Africa in both decades, though much less so over the period 2005‒2015 when, on average, emissions grew less rapidly than population. Over half of the 20 African top emitting countries shifted towards more carbon-intensive techniques. 3: Source of regional total emissions: Over the period 1995‒2015, intra-regional shares of emissions fell by seven, ten, and two percentage points to 84%, 75%, and 88% for Africa, Europe, and Asia, respectively. Africa's share of emissions originating from Asia rose from 4% to 11%. Europe's share of emissions originating from Africa and Asia rose from 2% and 8% to 4% and 16%, respectively 4: The export basket of Africa is skewed towards high CO2e intensity products. CO2 emission intensities are positively correlated with both the output upstreamness (OU) and input downstreamness (ID). The OU/ID indicator of position in a supply chain is negatively correlated with CO2 emission intensities within regions. The fit is higher at the sectoral level. For manufactures, being more upstream by 1% is associated with a higher emissions intensity of 0.61%. For the other sectors, the relation is negative, and largest for Agriculture and Construction.
Keywords: 330